2020
DOI: 10.3899/jrheum.201017
|View full text |Cite
|
Sign up to set email alerts
|

Concerns, Healthcare Use, and Treatment Interruptions in Patients With Common Autoimmune Rheumatic Diseases During the COVID-19 Pandemic

Abstract: Objective To assess concerns and healthcare-related behaviors of patients with autoimmune rheumatic diseases during the COVID-19 pandemic. Methods Adults from the United States with rheumatoid arthritis (RA), psoriatic arthritis (PsA), ankylosing spondylitis (AS), and systemic lupus erythematosus (SLE) from the ArthritisPower Patient-Powered Research Network and CreakyJoints patient community completed surveys. Concerns and behaviors were compared among patients with different autoimmune conditions, disease-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 14 publications
4
73
0
1
Order By: Relevance
“…We found that 10% of patients receiving immunomodulatory medications had stopped one of their medications because of concerns about COVID‐19, even if they were well with no COVID‐19 diagnosis or respiratory illness. Most medication interruptions were not recommended by a physician, similar to results from previous studies (10–12,22,23). Guidance from the American College of Rheumatology recommends not stopping medications unless patients have contracted or been exposed to severe acute respiratory syndrome coronavirus 2, although this guidance was first published in April 2020 and was not available when many patients answered their surveys (24).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We found that 10% of patients receiving immunomodulatory medications had stopped one of their medications because of concerns about COVID‐19, even if they were well with no COVID‐19 diagnosis or respiratory illness. Most medication interruptions were not recommended by a physician, similar to results from previous studies (10–12,22,23). Guidance from the American College of Rheumatology recommends not stopping medications unless patients have contracted or been exposed to severe acute respiratory syndrome coronavirus 2, although this guidance was first published in April 2020 and was not available when many patients answered their surveys (24).…”
Section: Discussionsupporting
confidence: 85%
“…We also found that patients receiving a biologic or JAKi were more likely to stop a medication (11,27), perhaps reflecting greater concern among this population and the perception that these medications may place patients at higher risk of complications of COVID‐19. Interestingly, older patients were less likely to have stopped medications, even though these patients are at greater risk of severe COVID‐19.…”
Section: Discussionmentioning
confidence: 81%
“…2). Previous chronic conditions, such as hypertension, 26 arthritis, 27 cancer, 28 epilepsy, 29 and neurodevelopmental disorders in children, 30 were the clinical topics of the investigations. The following factors were repeatedly observed: elderly, 31 women, 28,32 blacks, 26 and mental health of immigrants.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Concerns, healthcare-related behaviors and psychological impact of COVID-19 pandemic among patients with rheumatic diseases and in particular with SLE have been investigated by several works, reporting a trend towards remarkable psychological distress, however with contrasting results; more specifically, the effect of restrictive measures among the same populations has been less analysed. 15–19 …”
Section: Discussionmentioning
confidence: 99%